Implementasi Routing Dinamis pada Wireless Sensor Network menggunakan Modul Komunikasi LoRa - Mahardika Putra Utama; Dany Primanita Kartikasari; Aditya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The development of the WSN (Wireless Sensor Network) concept on the Internet of Things allows communication to be carried out wirelessly so as to help node mobility. Nodes that can move freely to move away from the gateway can cause communication to be interrupted so that a relay is needed as an intermediary for data transmission. Other nodes can be used to become a relay that helps bridge data transmission between nodes and gateways and utilizes multihop communication. So that each relay is responsible for sending its own data and forwarding data to other nodes that are not in the range of the gateway. In addition, this multihop concept can increase the range of wireless communication modules by utilizing other nodes as relays. A node that is not directly connected to the gateway must be able to find a routing path to get to the gateway. The path chosen must be the shortest path, so we need a routing protocol that can collect existing network information and choose the shortest path to get to the gateway. The routing protocol that is created must also be dynamic so that it can adapt to changes in the network because nodes on the network can move freely, so the arrangement of routing paths can change. There are two tests carried out to measure the feasibility of the system made, namely functional testing and performance testing. In functional testing the system can run well where nodes can collect all network information and choose the shortest path, send sensor data, forward sensor data from other nodes, and adapt to network changes such as disconnection of the selected path. Performance testing is conducted to test the ability of the system based on convergence time, packet delivery ratio, and delay with the effect of distance, number of hops, and delivery time intervals. The results of the functional testing of the node managed to meet all the requirements that have been determined. In the results of testing the performance of node convergence time it takes 7,365 seconds at a distance of 50 meters to get network information, while at a distance of 100 meters it takes 10,807 seconds. Then in the packet loss performance test, the lowest percentage is at a distance of 100 meters and the number of 1 hop jumps is 6% and the highest percentage is at a distance of 50 meters and the number of 3 hops jumps is 22%. In testing the delay performance, the lowest value is obtained at a distance of 50 meters and the number of 1 hop jumps is 276ms and the highest value at a distance of 100 meters 3 hops is 755ms.